2019
DOI: 10.18203/2320-6012.ijrms20195529
|View full text |Cite
|
Sign up to set email alerts
|

Body image perception, eating attitude and influence of media among undergraduate students of medical college in Delhi: a cross sectional study

Abstract: Background: Body image perception is being shaped by unrealistic ideals portrayed in the media. Body dissatisfaction is one of the most consistent and robust risk factors for eating disorders, low self-esteem, depression, and obesity. Therefore, the objective of the current study is to ascertain the body image perception, abnormal eating attitudes and the role of media among undergraduate students of a medical college in Delhi, India.Methods: Cross-sectional study on 370 undergraduate medical students of Vardh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 24 publications
2
11
1
1
Order By: Relevance
“…Table 1 shows the descriptive statistics of the study variables. Participants indicated higher body dissatisfaction (22.81 ± 9.261) when compared to previous research among Indians conducted pre-lockdown (20.43 ± 8.69) (Sharma et al, 2019). The fat talk levels were however lower (18.61 ± 6.701) compared to American undergraduate women (22.48 ± 3.69) (Ambwani et al, 2017).…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…Table 1 shows the descriptive statistics of the study variables. Participants indicated higher body dissatisfaction (22.81 ± 9.261) when compared to previous research among Indians conducted pre-lockdown (20.43 ± 8.69) (Sharma et al, 2019). The fat talk levels were however lower (18.61 ± 6.701) compared to American undergraduate women (22.48 ± 3.69) (Ambwani et al, 2017).…”
Section: Resultscontrasting
confidence: 54%
“…The total score was calculated by adding each item score (ranging from 30 to 150). This scale has been used in the Indian context, and has shown high reliability, internal consistency, and convergent validity (Warren et al, 2013;Sharma et al, 2019). The Cronbach alpha calculated for the present study was 0.925.…”
Section: Tools Usedmentioning
confidence: 71%
“…In a study of university students who lived in the east of Turkey, the authors reported that 20.8% of students tend to eating behaviors disorder (Devran, 2014). It was determined that 21.1% of the medical students were prone to eating behavior disorder in the study conducted by Sharma et al (2019). University students are a group at risk due to changes in lifestyle and nutritional habits.…”
Section: Discussionmentioning
confidence: 99%
“…The study titled "Body image perception, eating attitude and influence of media among undergraduate students of medical college in Delhi: a cross sectional study" was conducted by Sharma, Singh, Tiwari, and Chauhan (2019). The aim of the study is to determine body image perception, abnormal eating attitudes and the role of the media among undergraduate students of a medical school in Delhi, India.…”
Section: Supplicationmentioning
confidence: 99%